DESIGNING "JUNI’S COLOURFUL CLASSROOM", THE EDUCATIONAL ILLUSTRATED BOOK TO INTRODUCE DIVERSITY TO CHILDREN - Kurnianto, Sabrina Ramadhian; Arumsari, Rizki Yantami; Nurbani, Sri (eProceedings of Art & Design, 2024)
Racism has plagued humanity for centuries, persisting despite entering new eras of civilization. In the form of bullying, it remains a threat to students. Research unequivocally demonstrates that race-based bullying in schools is a significant concern today. This type of bullying, fueled by racial differences, detrimentally affects children's well-being and hinders their social and academic development. Thus, the research aims to design an engaging and informative illustration book promoting acceptance and understanding of racial diversity, with the goal of preventing racially motivated bullying. Based on interviews and research, the book is identified as an effective tool against racism that fuels such bullying. The paper comprehensively reviews literature on racism, race-based bullying, and educational interventions, forming a strong theoretical basis for the children's illustration book design. The research methodology involves a message design phase, including interviews with Indonesian Child Protection Commission (KPAI) representatives and experienced illustrators. This step ensures the resulting book's effectiveness for the target audience, children aged 6 to 9. The study emphasizes early education's role in promoting inclusivity, respect, and appreciation for diverse races and ethnicities. The illustration book will feature visually captivating illustration, distinct and diverse characters, and an effective easy-to-follow storyline. This design outcome is anticipated to give children with essential knowledge to address and transform their perspectives and behaviors toward diversity, racism, and the establishment of a harmonious, accepting school environment. Keywords: racism, raciall motivated bullying, diversity, children’s illustration book, edutainment.